Correction of hypovolemia with crystalloid fluids: Individualizing infusion therapy. Issue 4 (July 2015) - Liamis, George; Filippatos, Theodosios D.; Elisaf, Moses S.
Abstract: Many situations in clinical practice involving patients with hypovolemia or acutely ill patients usually require the administration of intravenous fluids. Current evidence shows that the use of crystalloids should be considered, since most colloids and human albumin are usually associated with increased adverse effects and high cost, respectively. Among crystalloids, the use of normal saline is implicated with the development of hyperchloremic metabolic acidosis and renal vasoconstriction. These observations have led many authors to propose balanced solutions, mainly Lactated Ringer's, as the infusate of choice. However, although the restoration of volume status is the primary target in hypovolemic state, the correction of any associated acid–base or electrolyte disorders that frequently coexist is also of vital importance. This review presents specific situations that are common in daily clinical practice and require targeted infusate therapy in patients with reduced volume status. Furthermore, the review presents an algorithm aiming to help clinicians to make the best choice between normal or hypotonic saline and lactated Ringer's infusates. Lactated Ringer's infusate should not be given in patients with severe metabolic alkalosis, lactic acidosis with decreased lactate clearance, or severe hyperkalemia, and in patients with traumatic brain injury or at risk of increased intracranial pressure. The optimal choice of infusate should be guided by the cause of hypovolemia, the cardiovascular state of the patient, the renal function, as well as the serum osmolality and the coexisting acid–base and electrolyte disorders. Clinicians should be aware of any coexisting disorders in patients with hypovolemia and guide their choice of infusate treatment based on the overall picture of their patients.